Chrystianizacja Słowian połabskich - Sprutta, Justyna (Annales Missiologici Posnanienses, 2020)
The Polabian Slavs were the last refuge of paganism in the Slavic region. They survived until 1168, because then Rugen, the last pagan bastion of the Slavs after the destruction of Radgosc, was conquered by Waldemar I, king of Denmark. The Polabian Slavs put up the longest resistance to Christianization, seeing it as a threat to their identity, nationality and tradition, of which the pagan cult was an important part. Even in 1147 a crusade was organized against the pagan Polabians, for which St. Bernard of Clairvaux called. The world of pagan Slavs ended with the moment of fall of Rügen and its Arkona, which became the centre of Slavic pagan cult after Radogosc. Two or three centuries later, Polabian Slavs were germanized, losing their nationality and thus becoming the part of Germany.